2008
DOI: 10.1038/sj.hdy.6801096
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic survival analysis of trypanotolerance QTL in mice

Abstract: A marker-assisted introgression (MAI) experiment was conducted to transfer trypanotolerance quantitative trait loci (QTL) from a donor mouse strain, C57BL/6, into a recipient mouse strain, A/J. The objective was to assess the effect of three previously identified chromosomal regions on mouse chromosomes 1 (MMU1), 5 (MMU5) and 17 (MMU17) in different genetic backgrounds on the survival pattern following infection with Trypanosoma congolense. An exploratory data analysis revealed a biphasic pattern of time to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Identifying QTL act at different time points during challenge i.e. early v.s late phase was reported, earlier with trypanosome infection [ 28 ]. This is not surprising machines knowing that the host innate and adaptive immunity systems act at different time points during infection.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying QTL act at different time points during challenge i.e. early v.s late phase was reported, earlier with trypanosome infection [ 28 ]. This is not surprising machines knowing that the host innate and adaptive immunity systems act at different time points during infection.…”
Section: Discussionmentioning
confidence: 99%
“…resistance to trypanosomosis in mice, Koudandé et al 2008). However, these QTLs are only suggestive and might not be confirmed.…”
Section: Lg1mentioning
confidence: 96%
“…It is not unexpected to find phase-specific QTLs, as mechanisms of disease resistance can be biphasic or even multiphasic (e.g. resistance to trypanosomosis in mice, Koudandé et al 2008). A first line of Table 3 Oxford plot comparing the sea bream linkage and RH map.…”
Section: Lg11mentioning
confidence: 99%
“…A study by Koudande et al . [ 63 ] used marker-associated introgression to transfer trypanotolerance QTLs from a donor mouse strain into a recipient mouse strain. The study showed that the introgressed mice had improved survival time to challenge than the recipient mice.…”
Section: Trypanotolerance In Livestockmentioning
confidence: 99%